Faktor yang Berhubungan Dengan Kepuasan Pasien Terhadap Pelayanan BPJS - Putri, Yelmi Reni; Nurhayati, Nurhayati; Zulfikar, Zulfikar (REAL in Nursing Journal, 2020)
Background: A survey of 10 BPJS card user’s patients who visited the Emergency Room dr. AchmadDarwisSuliki Hospital, it is known that 50% said lack of socialization, 40% felt slow to get services, and 60% did not know about BPJS policy rules regarding illnesses and health problems caused by BPJS. The purpose of the study was to determine factors related to patient satisfaction with BPJS services. Method: Analytical research methods with cross sectional approach. The population is all patients using BPJS cards who visited the Emergency Room of Dr. Achmad Darwis Hospital, with an average of 587 people per month. A sample of 100 people was taken accidentally. Results: Factors known to be related to patient satisfaction were communication / outreach (p = 0.006 and OR = 4.031), health care (HR) (p = 0.028 and OR = 2.957) and policy rules (p = 0,000 and OR = 36,694). It was concluded that there was no connection infrastructure with patient satisfaction. Conclusion: Therefore, it is expected that workers in the emergency room in order to be able to socialize BPJS services to patients using BPJS cards, by giving brochures or leaflets about health problems that can be borne by BPJS.Keywords: Socializations, Resources, Facilities, Policy, Satisfaction, BPJS